2022
DOI: 10.1002/mas.21812
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry for the study of adipocyte cell secretome in cardiovascular diseases

Abstract: Adipose tissue is classically considered the primary site of lipid storage, but in recent years has garnered appreciation for its broad role as an endocrine organ, capable of remotely signaling to other tissues to alter their metabolic program. The adipose tissue is now recognized as a crucial regulator of cardiovascular health, mediated by the secretion of several bioactive products, with a wide range of endocrine and paracrine effects on the cardiovascular system. Thanks to the development and improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 125 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…Mass spectrometry-based proteomic studies of adipocyte cell and tissue secretomes have identified hundreds of differentially expressed proteins (see Gianazza et al . [ 17 ] for a recent comprehensive review on the subject). The most relevant study for our work is on proteomic profiling of conditioned medium collected from primary human adipocytes [ 18 ].…”
Section: Fractionation Of Adipocyte-conditioned Medium Reveals Factor...mentioning
confidence: 99%
“…Mass spectrometry-based proteomic studies of adipocyte cell and tissue secretomes have identified hundreds of differentially expressed proteins (see Gianazza et al . [ 17 ] for a recent comprehensive review on the subject). The most relevant study for our work is on proteomic profiling of conditioned medium collected from primary human adipocytes [ 18 ].…”
Section: Fractionation Of Adipocyte-conditioned Medium Reveals Factor...mentioning
confidence: 99%
“…date biofluid biomarkers for non-invasive cancer detection and disease monitoring [4][5][6]. To identify the cancer proteins secreted by cancer cells, mass spectrometry-based secretome proteomics has emerged as a powerful unbiased approach for marker identification [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%